A bivalent role of TIP60 histone acetyl transferase in human cancer. (December 2015) - Judes, Gaëlle; Rifaï, Khaldoun; Ngollo, Marjolaine; Daures, Marine; Bignon, Yves-Jean; Penault-Llorca, Frédérique; Bernard-Gallon, Dominique
Acetylation is a major modification that is required for gene regulation, genome maintenance and metabolism. A dysfunctional acetylation plays an important role in several diseases, including cancer. A group of enzymes-lysine acetyltransferases are responsible for this modification and act in regulation of transcription as cofactors and by acetylation of histones and other proteins. Tip60, a member of MYST family, is expressed ubiquitously and is the acetyltransferase catalytic subunit of human NuA4 complex. This HAT has a well-characterized involvement in many processes, such as cellular signaling, DNA damage repair, transcriptional and cellular cycle. Aberrant lysine acetyltransferase functions promote or suppress tumorigenesis in different cancers such as colon, breast and prostate tumors. Therefore, Tip60 might be a potential and important therapeutic target in the cancer treatment; new histone acetyl transferase inhibitors were identified and are more selective inhibitors of Tip60.